Elevational divergence and clinal variation in floral color and leaf chemistry in Silene vulgaris. Issue 8 (12th August 2016) - Berardi, Andrea E.; Fields, Peter D.; Abbate, Jessica L.; Taylor, Douglas R.
Abstract : PREMISE OF STUDY: Environmental heterogeneity over a species range can lead to divergent selection among populations, leading to phenotypic differences. The plant flavonoid pathway controls key reproductive and defense‐related traits and responds to selection and environmental stressors, allowing for hypotheses about phenotypic divergence across environmental gradients. We hypothesized that with increasing elevation, more flavonoids would be produced as a response to increased UV radiation and that plants would be better defended against herbivores. METHODS: We measured floral color, flavonoids, and herbivory in natural populations of Silene vulgaris (Caryophyllaceae) along elevational transects in the French Alps. We correlated phenotypes with environmental variables and calculated genotypic divergence ( F ST ) to compare with phenotypic divergence ( P ST ). KEY RESULTS: We found significant phenotypic variation in S. vulgaris along elevational gradients. Strong positive correlations were observed between floral color, leaf non‐anthocyanidin flavonoid concentration, and elevation. Floral anthocyanin and leaf non‐anthocyanidin flavonoid phenotypes negatively covaried with temperature and precipitation seasonality. Comparisons of P ST to F ST provided evidence for stabilizing selection on floral color among transects and divergent selection along the elevational gradient. CONCLUSIONS: Flavonoid production increases along elevational gradients in S. vulgaris, with clinal variation in calyx anthocyanins and increasing leaf non‐anthocyanin flavonoid concentrations. Despite the photoprotective and antiherbivore properties of some flavonoids, flavonoid production in flowers and leaves was correlated with population microclimatic variables: temperature and precipitation. Taken together, the results suggest that different flavonoid groups are targeted by selection in different tissues and provide evidence for divergent patterns of selection for flavonoids between high and low elevations.